2014
DOI: 10.3390/jlpea4020153
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Charge Trapping Type SOI-FinFET Flash Memories with Different Blocking Layer Materials

Abstract: The scaled charge trapping (CT) type silicon on insulator (SOI) FinFET flash memories with different blocking layer materials of Al 2 O 3 and SiO 2 have successfully been fabricated, and their electrical characteristics including short-channel effect (SCE) immunity, threshold voltage (V t ) variability, and the memory characteristics have been comparatively investigated. It was experimentally found that the better SCE immunity and a larger memory window are obtained by introducing a high-k Al 2 O 3 blocking la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
3
1
Order By: Relevance
“…11(a). Actually, the marked V t roll-up in the erase state in the FG-type TF-ANO and RF-ANO devices is slightly different from that in the previously reported CT-type SOI-FinFET flash memory with an Al 2 O 3 blocking layer (31). In the case of the CT-type SOI-FinFET flash memory, the V t roll-up in both the erase and program states after 10 k cycle operations should be predominated by tunnel oxide degradation.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…11(a). Actually, the marked V t roll-up in the erase state in the FG-type TF-ANO and RF-ANO devices is slightly different from that in the previously reported CT-type SOI-FinFET flash memory with an Al 2 O 3 blocking layer (31). In the case of the CT-type SOI-FinFET flash memory, the V t roll-up in both the erase and program states after 10 k cycle operations should be predominated by tunnel oxide degradation.…”
Section: Resultscontrasting
confidence: 79%
“…However, the fin channel shape and interpoly dielectric (IPD) material effects on the electrical characteristics of FG-type SOI-FinFET flash memories have not been investigated sufficiently, although the high-k dielectric stacks and barrier-engineered multilayers have been used as an IPD layer for improving the gate coupling of the conventional bulk planar FG-type flash memories (27)(28)(29)(30). Very recently, we have also reported CT-type SOI-FinFET flash memories with different blocking layer materials of Al 2 O 3 and SiO 2 , and confirmed that introducing an Al 2 O 3 blocking layer instead of a SiO 2 one is very efficient for enlarging memory windows owing to the high-k effect of the Al 2 O 3 blocking layer (31).…”
Section: Introductionsupporting
confidence: 55%
“…Actually, the marked V t roll-up in the erase state in the FG-type TF-ANO and RF-ANO devices is slightly different from that in the previously reported CT-type SOI-FinFET flash memory with an Al 2 O 3 blocking layer. 44) In the case of the CT-type SOI-FinFET flash memory, the V t roll-up in both the erase and program states after 10 k cycle operations should be predominated by tunnel oxide degradation. However, in the case of the FGtype TF-ANO and RF-ANO devices, the marked V t roll-up especially at the erase state after 10 k cycle operations should be related to the insufficient detrapping of electrons through an ANO-stacked IPD layer, which will be discussed later.…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42][43] Very recently, we have also reported CT-type SOI-FinFET flash memories with different blocking layer materials of Al 2 O 3 and SiO 2 , and confirmed that introducing an Al 2 O 3 blocking layer instead of a SiO 2 one is very efficient for enlarging memory windows owing to the high-k effect of the Al 2 O 3 blocking layer. 44) To further our study, in this work, we fabricated scaled FG-type SOI-FinFET flash memories with different fin channel shapes and IPD materials, and compared their electrical characteristics including V t variability, program= erase (P=E) speed, memory window, endurance, and data retention at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…= 2 � 4 where = 1.875,4.694,7.885. 11 Therefore the resonance frequency of a simply supported cantilever beam can be calculated using (1) where is the Young's modulus, is the moment of inertia, is the length of the cantilever, is the width of the cantilever, is the mass per unit length of the cantilever beam, and = 1.875 is the eigenvalue for the fundamental vibration mode.…”
Section: Fig 3 Cantilever Beam With Rectangular Cross Section Undermentioning
confidence: 99%